Artifacts in oral histopathology: what a clinician should know - Battistelli, Luísa Souza; Ribeiro, Jaqueline Lemes; Kaminagakura, Estela; Anbinder, Ana Lia [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
The e-book “Artifacts in oral histopathology: what a clinician should know” addresses, in a practical and didactic manner, the main artifacts that may occur in oral biopsies and their impact on histopathological diagnosis. It defines artifacts as artificial alterations that may mimic diseases or hinder the interpretation of tissue samples. The material highlights the role of the dentist in preventing these errors, describing artifacts related to biopsy technique, such as injection of anesthesia into the lesion, thermal damage, tissue compression, suction, and inadequate sampling, as well as presenting measures to avoid them. It also emphasizes the importance of proper fixation, including timing, type, and volume of the fixative, providing practical guidance to preserve tissue integrity. This is an educational resource aimed at improving diagnostic quality in oral pathology.
Keywords: Diagnosis, oral; artifacts; biopsy; Artefatos; Biópsia; Diagnóstico bucal